A diatom-based biohybrid microrobot with a high drug-loading capacity and pH-sensitive drug release for target therapy. (December 2022) - Li, Mengyue; Wu, Junfeng; Lin, Daojing; Yang, Jia; Jiao, Niandong; Wang, Yuechao; Liu, Lianqing
Abstract: Targeted delivery is a promising mean for various biomedical applications, and various micro/nano robots have been created for drug delivery. Mesoporous silica has been shown to be successful as a drug delivery carrier in numerous studies. However, mesoporous silica preparation usually requires expensive and toxic chemicals, which limits its biomedical applications. Diatoms, as the naturally porous silica structure, are promising substitutes for the artificial mesoporous silica preparation. However, the current studies utilizing intact diatom frustules as drug delivery packets lack flexible and controllable locomotion. Herein, we propose a biohybrid magnetic microrobot based on Thalassiosira weissflogii frustules (TWFs) as a cargo packet for targeted drug delivery using a simple preparation method. Biohybrid microrobots are fabricated in large quantities by attaching magnetic nanoparticles (Fe3 O4 ) to the surface of diatoms via electrostatic adsorption. Biohybrid microrobots are agile and controllable under the influence of external magnetic fields. They could be precisely controlled to follow specific trajectories or to move as swarms. The cooperation of the two motion modes of the biohybrid microrobots increased microrobots' environmental adaptability. Microrobots have a high drug-loading capacity and pH-sensitive drug release. In vitro cancer cell experiments further demonstrated the controllability of diatom microrobots for targeted drug delivery. The biohybrid microrobots reported in this paper convert natural diatoms into cargo packets for biomedical applications, which possess active and controllable properties and show huge potential for targeted anticancer therapy. Statement of significance: In this study, diatoms with good biocompatibility were used to prepare biohybrid magnetic microrobots. Compared with the current diatom-based systems for drug delivery, the microrobots prepared in this study for targeted drug delivery have more flexible motion characteristics and exhibit certain swarming behaviors. Under the same magnetic field strength, by changing the magnetic field frequency, the movement state of the diatoms can be changed to pass through the narrow channel, so that it has better environmental adaptability. Graphical abstract: Image, graphical abstract